Analysis of Teacher Difficulties in Teaching Physics Courses in MAN 1 Konawe Selatan - Halmuniati Halmuniati; Muhammad Dani Saputra; Nurfaidah Syam; La Wui (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2022)
This research was conducted with the aim of knowing the process of implementing physics learning, what factors cause teacher teaching difficulties and solutions to the teacher's difficulties. This research was conducted at MAN 1 Konsel with 3 physics teachers as informants who used descriptive methods through a qualitative approach. Data collection techniques with observation, interviews and documentation. The data analysis technique uses data collection, data reduction, presentation, and drawing conclusions or verification. From the results of the study, it was found that at the time of implementation of learning, it was found that all teachers had quite a difficulty in developing teaching materials. There are 4 factors that influence the difficulty of teachers in teaching physics, namely the low basic mathematical ability of students, inadequate facilities and infrastructure, the learning methods used by schools are less varied and innovative, and the time allocation is still lacking in achieving learning objectives. So the solution to answer the difficulties they are experiencing is that the teacher must involve students with good mathematical abilities to help their friends, using simple laboratory tools that the teacher can make themselves by using used materials or by using virtual laboratories, the teacher must also combine various methods and techniques. Innovative learning model, strives to maximize the available time allocation.